Analisis Kinerja Keuangan dengan Menggunakan Rasio Likuiditas dan Profitabilitas pada Bursa Efek Indonesia PT. Unilever TBK Periode 2019-2023 - Muzauwir Almadani, Sultan; Zuraidah; Rusnaidi (Politeknik Kampar, 2025)
This research focuses on companies in Indonesia, particularly in Home and Personal Care and Foods & Ice Cream sectors, analyzing the financial performance of PT. Unilever Indonesia Tbk from 2019 to 2023 using liquidity and profitability ratios. The aim is to assess whether its financial performance has improved or declined in comparison to industry standards. The study uses secondary data, specifically time-series data collected annually, and employs a descriptive analysis method. The results indicate that the liquidity ratios, including Current Ratio (CR) and Quick Ratio (QR), have fluctuated, with values both above and below industry standards. The Cash Ratio, however, consistently exceeded the industry average, reflecting a strong return on cash sales. Regarding profitability, the Net Profit Margin (NPM) and Return on Assets (ROA) showed fluctuating performance, remaining below industry averages, indicating inconsistent financial management. However, the Return on Equity (ROE) aligned with industry standards, showcasing the company’s ability to effectively generate income from its equity.